Assessment of paper-based MoS2 FET for Physically Unclonable Functions. (August 2022) - Vatalaro, Massimo; De Rose, Raffaele; Lanuzza, Marco; Magnone, Paolo; Conti, Silvia; Iannaccone, Giuseppe; Crupi, Felice
Highlights: Two-dimensional (2D) materials as emerging technology for next-generation electronics. MoS2 -based field-effect transistors (FETs) on paper substrate for flexible electronics. Look-up-table (LUT) based Verilog-A model calibrated on measurements of fabricated devices. Circuit simulations of cryptographic primitives such as physically unclonable functions (PUFs) Potential of paper-based MoS2 FETs as building blocks for hardware security applications. Abstract: Two-dimensional (2D) materials are recognized as a promising beyond-CMOS technology thanks to their attractive electrical and mechanical properties, which make them particularly suitable for flexible electronics. This work investigates molybdenum disulfide (MoS2 ) based field-effect transistors (FETs) fabricated on paper substrate to design hardware-security primitives such as Physically Unclonable Functions (PUFs). Circuit simulations have been performed by using a look-up-table (LUT) based Verilog-A model calibrated on electrical measurements of fabricated devices. Obtained results prove the potential of paper-based MoS2 FETs as building blocks for next-generation flexible electronics in the field of hardware security.